Atomic Cobalt on Defective Bimodal Mesoporous Carbon toward Efficient Oxygen Reduction for Zinc–Air Batteries. Issue 9 (11th January 2019) - Lyu, Xiao; Li, Gen; Chen, Xiaokang; Shi, Bowen; Liu, Jizi; Zhuang, Linzhou; Jia, Yi
Abstract: Single‐atom catalysts (SACs) with maximum atom‐utilization efficiency and distinctive properties are emerging as a new frontier in the field of catalysis. Herein, a new strategy for synthesizing stable Co single atoms with content of about 1.52 wt% on defective bimodal mesoporous carbon materials (A‐Co@CMK‐3‐D) is reported. The dispersion and coordination structures of atomic Co species at carbon defect sites are confirmed by both aberration‐corrected high‐resolution transmission electron microscopy (AC‐HRTEM) and X‐ray absorption spectrometry, respectively. The obtained catalyst exhibits efficient electrochemical performance on oxygen reduction reaction (ORR) in an alkaline electrolyte with a half‐wave potential (0.835 V vs RHE), which is comparable to that of Pt/C (0.839 V vs RHE). Furthermore, the Zn–air batteries (ZABs) fabricated by this electrocatalyst display a superior discharging and charging performance with long‐term durability. This work provides a new approach on optimizing SAC‐based carbon materials from multiscale principles (simultaneous regulation of electronic structure and hierarchical morphology) to boost ORR reactivity. Abstract : Atomic Co‐doped hierarchical mesoporous carbon as an efficient and stable oxygen reduction reaction (ORR) catalyst is successfully fabricated via defect engineering. The obtained catalyst exhibits Pt comparable activity for ORR, and the assembled Zn–air battery shows excellent discharge capacity and cycling stability. This work may guide the design of single‐atom catalysts under multiscale regulation, including electronic modulation, metal‐defect coordination, and morphological characteristics.